Giant cell tumor of the bone with fatal pulmonary metastasis: A case report - Mohamad Taha; Saadia A. Faiz; Pushan Jani; Jing Liu; Yasir D. Ali; Mohammad Asim Amjad (SAGE Open Medical Case Reports)
Giant cell tumors of the bone are typically benign, locally aggressive lesions that rarely metastasize. In this report, we describe the case of a 48-year-old woman presenting with a giant cell tumor of the bone of the hip joint, which demonstrated aggressive histological features and recurrent behavior. The patient developed multiple unresectable pulmonary metastases despite several wide local excisions. Although pulmonary metastases from giant cell tumors of the bone are usually associated with a relatively favorable prognosis, guidelines for the optimal treatment of metastatic giant cell tumors of the bone remain limited. This case highlights the unpredictable nature of giant cell tumors of the bone and emphasizes the need for alternative treatment options in those with resistance to traditional therapies.